Modernisasi Dan Perubahan Sosial Budaya Suku Bajo Dalam Perlindungan Dan Pemanfaatan Sumberdaya Laut Di Sanana Utara Provinsi Maluku Utara - Gorontalo, Rifani . (JURNAL ILMIAH SOCIETY, 2015)
Modernization of a society can occur if a positive impact for instance on modern settlements, life and technological equipment. Changes among Bajo North Sanana especially at customs due to the absence of delivery systems in the form of inheritance from generation to generation to the younger generation, other factors that could be habituation concept of education and the economy. So as to change the lifestyle of the people of North Sanana of Â Bajo from the traditional to the modern lifestyle. The results showed that the modernization of the general public in Bajo in North Sanana is affecting the change of the customs that have been used since. As for some of the factors triggering the change are as follows: The modern settlement could lead to competition among North Sanana of Bajo community in terms of building their homes, Economic Improvement is helpful to community`s income of Bajo community in North Sanana, because now people are able to live independently in Bajo as traders, as well as opening other small businesses, With the North Sanana Bajo village education so that they can help their children to attend school and continue on to Higher Education, The means of modern life, especially in the fishing equipments that can help the village of Bajo in North Sanana ease when searching for sustenances in the sea, because the work average in Bajo are as fishermen. Keywords: Cultural, Social Change, Traditional, Modern